Investigation of Scheduling Techniques for Uncertain Conditions - Taiba Zahid; Mathias Kühn; Michael Völker; Thorsten Schmidt (Operational Excellence in Logistics and Supply Chains: Optimization Methods, Data-driven Approaches and Security Insights. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 22, 2015)
The traditional methods and techniques employed in operational management seem unable to provide solutions that can be actually practiced. This insufficiency is caused by the uncertainties and delays which are faced in practice. The potential causes of these uncertainties are usually internal (inadequate resources, faults and breakdowns) and external (material shortfall or low quality) environment. These realizations have forced researchers in the past decade to find stable solutions which have ability to remain insensitive to these disturbances and provide solutions which can be practiced. The present study investigates the methods adopted to provide such flexible and robust solutions. The aim is to identify and categorize the methodologies in this nondeterministic field and compare their performance with the static ones. In addition to that, a detail analysis of techniques proposed in the literature is delivered, which implies their limitations, assumptions and applications areas in scheduling.
10419/209191; https://econpapers.repec.org/RePEc:zbw:hiclpr:22
Keywords: 650; Scheduling; Uncertainty; Robustness; Stochastic